Overview of Green Roof Technology as a Prospective Energy Preservation Technique in Arid Regions - Mahmoud, A. S. (Engineering, Technology & Applied Science Research, 2022)
Concerns about climate change and rising energy demands have grown as a result of fast population rise and global industrialization. The construction industry has a huge impact on the energy and environmental sectors, accounting for about 40% of global energy consumption and a large portion of overall territorial emissions. There is a need for a shift in mindset when it comes to energy usage, as well as enhanced energy efficiency approaches and radical energy efficiency initiatives. As an energy-saving solution, the green roof, also known as the living roof has suitability and environmental benefits on many levels, while also strengthening aesthetic features and provoking structural innovation. Moreover, drought-prone areas, e.g. Saudi Arabia, have significant household energy demands. The Saudi building sector consumes more than 76% of the country's total electric power generation. As a result, the purpose of this study is to provide a general overview of living roof technology and its potential in Saudi Arabia as an energy-saving strategy. An overview of the building envelope, the impact of cladding design considerations on power usage, the benefits of a living roof, cost-benefit analysis, green policies, and examples from other countries are included in the paper. Other environmental benefits, besides the energy-saving potential of living roofs, were shown to boost the quantitative benefits of the living roof idea. A more detailed study is needed, among other things, to evaluate the energy-saving potential of living roofs based on the weather of various locations.